Chlamydia trachomatis Strain Types Have Diversified Regionally and Globally with Evidence for Recombination across Geographic Divides - Smelov, Vitaly; Vrbanac, Alison; van Ess, Eleanne F.; Noz, Marlies P.; Wan, Raymond; Eklund, Carina; Morgan, Tyler; Shrier, Lydia A.; Sanders, Blake; Dillner, Joakim; de Vries, Henry J. C.; Morre, Servaas A.; et al. (Frontiers in Microbiology, 2017)
Chlamydia trachomatis (Ct) is the leading cause of bacterial sexually transmitted diseases (STD) worldwide. The Ct Multi Locus Sequence Typing (MLST) scheme is effective in differentiating strain types (ST), deciphering transmission patterns and treatment failure, and identifying recombinant strains. Here, we analyzed 323 reference and clinical samples, including 58 samples from Russia, an area that has not previously been represented in Ct typing schemes, to expand our knowledge of the global diversification of Ct STs. The 323 samples resolved into 84 unique STs, a 3.23 higher typing resolution compared to the gold standard single locus ompA genotyping. Our MLST scheme showed a high discriminatory index, D, of 0.98 (95% CI 0.97-0.99) confirming the validity of this method for typing. Phylogenetic analyses revealed distinct branches for the phenotypic diseases of lymphogranuloma venereum, urethritis and cervicitis, and a sub-branch for ocular trachoma. Consistent with these findings, single nucleotide polymorphisms (SNP) were identified that significantly correlated with each phenotype. While the overall number of unique STs per region was comparable across geographies, the number of STs was greater for Russia with a significantly higher ST/sample ratio of 0.45 (95% CI: 0.35-0.53) compared to Europe or the Americas (p<0.009), which may reflect a higher level of sexual mixing with the introduction of STs from other regions and/or reassortment of alleles. Four STs were found to be significantly associated with a particular geographic region. ST23 [p=0.032 (95% CI: 1-23)], ST34 [p=0.019 (95% CI: 1.1-25)]; and ST19 [p=0.0004 (95% CI: 1.7-34.7)] were significantly associated with The Netherlands compared to Russia or the Americas, while ST 30 [p=0.031 (95% CI: 1.1-17.8)] was significantly associated with the Americas. ST19 was significantly associated with The Netherlands and Russia compared with the Americans [p=0.0004 (95% CI: 1.7-34.7) and p=0.0058 (95% CI: 1.5-34.6), respectively]. Additionally, recombinant strains were ubiquitous in the data set [106 (32.8%)], although Europe had a significantly higher number than Russia or the Americas (p<0.04), the majority of which were from Amsterdam [43 (87.8%) of 49)]. The higher number of recombinants in Europe indicates selective pressure and/or adaptive diversification that will require additional studies to elucidate.